Community And Family-Based Intervention Strategies To Prevent Stunting: A Systematic Review - Puspitasari, Yunidar Dwi; Indarwati, Retno; Wahyuni, Silvya Dwi; Suraya, Andi Safutra (Universitas Tribhuwana Tunggadewi, 2025)
Stunting is a state of chronic malnutrition associated with nutritional insufficiency. Stunting can increase the risk of morbidity and mortality, hindering children's growth and development. Malnutrition in toddlers can also arise due to the cultural practices, eating habits, and social norms related to food intake. The role of the family and the community is very important in ensuring the success of stunting prevention programs. This study aimed to undertake a systematic review of the international literature on community-based interventions to prevent stunting in children under 5 years. We reviewed original quantitative research from Scopus, Science Direct, PubMed, and ProQuest using the keywords “community intervention” OR “family intervention” AND “stunting” AND “toddlers”. We conducted a critical appraisal using PRISMA guidelines on evidence documenting the community-based intervention or program as a strategy to reduce stunting in toddlers, between 1 January 2013 and 31 January 2023 with the inclusion criteria of English-language, full-text, open-access, quantitative studies. Thirteen peer-reviewed papers met the inclusion criteria. This review found that family-based intervention could improve child growth and community-based intervention could strengthen the community health systems. The existing evidence showed a positive impact of community and family-based intervention to prevent stunting. Family-strengthening interventions may have an impact on reducing stunting among children under 5 years.